PLANNING PROCESS OF PILOT BATCH PRODUCTION OF AN INNOVATIVE DRUG FOR CLINICAL TRIAL IN A PHARMACEUTICAL INDUSTRY - Harada, Lila M.; da Silva, Adriano Manicoba (Brazilian Journal of Operations & Production Management, 2016)
Purpose – Clinical trials are the most critical step in the process of drug development and evaluation to bring a new drug to market. The purpose of this article was to show an approach of the planning and production of a new innovative drug for a clinical study, based on the presentation of decision-making process in a national pharmaceutical industry. Design / methodology / approach - Through a case-study methodology, it was described the pilot batch production planning of a new drug for clinical trial, focusing on how the company evaluates the adequacy of the available systems at the manufacturing plant and how they use them in drug production planning process. Findings – A previous planning for clinical trial supplies production is determinant to decide the order, amount and timing of the products to be produced when the manufacturing plant is shared with the production of commercial products. Also, even in a small pilot batch production, there is a substantial waste of supplies during the process. Research Limitations / Implications – This study showed the production planning process of one investigational product with the recruitment of few patients for the clinical trial. However, the number of patients enrolled can reach thousands in many clinical trials, and it does need a more complex production planning to avoid wastes and try to reduce the process costs. Practical Implications - This article provides a picture of the production planning of clinical trial supplies chain under uncertainty and the decisions that affect the large-scale production of commercial drugs and the pilot batch production of experimental drugs. Originality / value - Although the results of clinical trials is the most significant source of uncertainty in the development process of any new drug, a good clinical supply planning and processes management can avoid or attenuate the imminent risk of process failure.